New geochronological constraints on the geological evolution of Espinhaço basin within the São Francisco Craton—Brazil - DANDERFER, André (2009)
The São Francisco Craton, in the central-eastern region of Brazil, is a cratonic fragment stabilized after the Rhyacian tectono-metamorphic event (2.25–2.05 Ga). Volcanic and sedimentary rocks of the Espinhaço (Paleo-to Mesoproterozoic) and São Francisco (Neoproterozoic) basins crop out on this craton. In the northern sector of the craton, the Espinhaço basin crops out in two domains: the Northern Espinhaço Range and the Chapada Diamantina, that are separated by the Paramirim Corridor, a Brasiliano/Pan African (650–500 Ma) deformation zone, which crosses the craton in NNW–SSE direction. The stratigraphic framework of the Northern Espinhaço is characterized by eight synthems that comprise units bound by unconformities, or stratigraphic discontinuities with regional extent over the Espinhaço basin. These synthems are: Algodão, São Simão, Sapiranga, Pajeú and Bom Retiro (lower interval), São Marcos and Sítio Novo (intermediate interval) and Santo Onofre (upper interval). For each interval the sedimentary processes, the depositional systems, the filling style of the basin and the tectonic settings were evaluated, based mainly on the facies association characteristics and their lateral/vertical changes. Zircon U–Pb SHRIMP and basin analysis studies carried out along the eastern border of the Northern Espinhaço Range provide a few new or improved anchors upon which the tectonic evolution of the Espinhaco basin can be pinned. We identified Statherian rifting in the São Simão Synthem, by dating volcanic rocks at 1.73 Ga. This is followed by a previously unknown, minor intracratonic rift phase within the São Francisco Craton, dated at circa 1.57 Ga through a volcanic unit within the Pajeú Synthem. The entire lower interval is cut by mafic intrusive dykes of which we dated one at 850 Ma, which we correlate with a Tonian rifting phase affecting the eastern part of the São Francisco craton, and related to the break-up of the Rodinia Supercontinent. Our data show that the development of the Northern Espinhaço Range spans a large time interval, and comprises a discontinuous series of tectonic events that gave rise to the formation of the various synthems and are punctuated by the extrusion of minor volcanic units and emplacement of dykes within the eastern part of the São Francisco Craton